2008
DOI: 10.1249/01.mss.0000321735.21347.7d
|View full text |Cite
|
Sign up to set email alerts
|

Precooling and Running Economy

Abstract: Right click to open a feedback form in a new tab to let us know how this document benefits you. Right click to open a feedback form in a new tab to let us know how this document benefits you.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(237 reference statements)
0
1
0
Order By: Relevance
“…RE incorporates both biomechanical as well as physiological parameters and is thought to account for differences between elite athletes who display similar VO 2max values (Bassett & Howley, 2000). Despite indications that precooling may benefit some determinants of RE such as oxygen uptake (Lee & Haymes, 1995), stride length (Folland et al, 2006), and neuromuscular function (Siegel et al, 2011), no differences were found, supporting the results of Winke and Yates (2008) who examined RE following ice slurry precooling. Thus, beneficial effects of precooling do not appear to present through improved RE while exercising for relatively short durations in the heat.…”
Section: Effects Of Coolingmentioning
confidence: 81%
“…RE incorporates both biomechanical as well as physiological parameters and is thought to account for differences between elite athletes who display similar VO 2max values (Bassett & Howley, 2000). Despite indications that precooling may benefit some determinants of RE such as oxygen uptake (Lee & Haymes, 1995), stride length (Folland et al, 2006), and neuromuscular function (Siegel et al, 2011), no differences were found, supporting the results of Winke and Yates (2008) who examined RE following ice slurry precooling. Thus, beneficial effects of precooling do not appear to present through improved RE while exercising for relatively short durations in the heat.…”
Section: Effects Of Coolingmentioning
confidence: 81%